2013
DOI: 10.1002/bjs.9225
|View full text |Cite
|
Sign up to set email alerts
|

Extent and completeness of mesorectal excision evaluated by postoperative magnetic resonance imaging

Abstract: Inadvertent residual mesorectum was commonly found on postoperative MRI, especially after partial mesorectal excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 20 publications
5
48
0
1
Order By: Relevance
“…Of those patients, 134 patients did not have a postoperative MRI performed (exclusion described elsewhere 19 ). Seventy-five patients who had an MRI were not assessed for bowel dysfunction using the LARS score, either due to no clinical follow-up or because of a non-reversed stoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those patients, 134 patients did not have a postoperative MRI performed (exclusion described elsewhere 19 ). Seventy-five patients who had an MRI were not assessed for bowel dysfunction using the LARS score, either due to no clinical follow-up or because of a non-reversed stoma.…”
Section: Resultsmentioning
confidence: 99%
“…19 In addition, patients who had undergone restorative sphincter-preserving surgery had their bowel function assessed using the LARS score 20 a minimum of one year following surgery, and when applicable, a minimum of six months following ileostomy reversal.…”
Section: Methodsmentioning
confidence: 99%
“…Bondeven et al [10] reported residual mesorectum in 36% of patients who, based on the size of the tumour, should have had a TME. However, the majority of these patients underwent open TME.…”
Section: Discussionmentioning
confidence: 99%
“…However, the laparoscopic approach for middle and lower rectum cancer is still a challenge even for experienced surgeons, especially in obese male patients [9]. Furthermore, Bondeven et al [10] demonstrated that residual mesorectum is present in 36% of patients who underwent open as well as laparoscopic surgery. Thus, a new kind of minimally invasive surgical procedure, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…15 The majority of LRs historically reflected inadequate mesorectal resection, 16 which is a common finding on postoperative MRI after partial mesorectal excision. 17 Currently, optimal quality-controlled surgery, in terms of TME in the trial setting, can be associated with LR rates of less than 10 %, whether patients receive RT or not. 7 Factors that compromise the performance of good-quality TME are well recognised and include patient-and disease-related aspects and the surgeon's case volume.…”
mentioning
confidence: 99%